Etika Bisnis dan Strategi Adaptif UMKM dalam Menghadapi Krisis 2030 di Era Pasar Bebas - Annisa Rahmah Herlin; Nurdyanti Choirunnisa Pane; Jeroh Miko (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This study aims to examine the role of business ethics and adaptive strategies in sustaining Micro, Small, and Medium Enterprises (MSMEs) amid the projected economic crisis in 2030 within a free-market era. MSMEs face challenges such as global competition, digital transformation, and rapidly shifting consumer preferences. The research employs a qualitative approach with a descriptive-analytical method and data collection through literature review. The results indicate that implementing strong business ethics, including transparency and social responsibility, can enhance consumer trust and customer loyalty. Furthermore, adaptive strategies such as digitalization, product innovation, and cost efficiency significantly improve MSMEs’ resilience during crises. The study highlights the importance of collaboration among MSME actors and stakeholders, along with the need for training and supportive regulations. By integrating ethical practices and adaptive strategies, MSMEs have a strong potential to survive and thrive amidst global economic dynamics.